Students’ Responses Towards the Teachers’ Strategies in Teaching Speaking In Tenth Grade At SMA Negeri 2 Parepare - Ikhsan, M. Nur; Sianna, Sianna; A, Nasrullah (La Parole : Journal of Language Teaching and Pedagogy, 2023)
In learning English, students tend to encounter issues with limited vocabulary and grammar, accuracy of pronunciation, fear of making mistakes while speaking, and other problems. These occurrences are influenced by several factors, one of which is the teacher's strategies. By employing suitable strategies aligned with students' needs and desires, the attainment of learning objectives can be facilitated. Based on this statement, the researcher analysed the strategies used by English teachers in teaching speaking skills and the students' responses to these strategies in the tenth-grade classes at SMA Negeri 2 Parepare. The objectives of this study are to investigate the strategies employed by English teachers in teaching speaking skills, and to determine the students' responses to the strategies utilized by the teacher in teaching speaking skills. The research design employed in this study is qualitative descriptive research. The subjects of this study consist of tenth-grade English teachers and students of class X Mipa 1 in SMA Negeri 2 Parepare. The researcher selected only one tenth-grade English teacher and 15 students from class X Mipa 1 as participants. Data for this research was collected through questionnaires administered to the students and supported by interviews conducted with the teacher to ensure balanced results. The collected data was analysed using Miles and Huberman's theory, which includes data reduction, data display, and drawing conclusions. Furthermore, to establish the validity of the data, this study employed methodological triangulation.The results of this study indicate that English teachers implement various plans, methods, approaches, and a variety of designed activities to achieve learning objectives. English teachers employ diverse methods in teaching speaking, such as discussions, role plays, storytelling, and story completion. These strategies can assist students in becoming more active and enthusiastic about learning to speak English. The instructional strategies employed include the use of group work strategies, employing language that is easily comprehensible to students, providing multiple interactions or training in discussion skills, and encouraging students to communicate in the target language. These strategies can help keep students motivated and confident. Furthermore, students' responses to the implemented strategies in learning to speak indicate that they are more engaged in classroom discussions and enjoy learning English due to teachers consistently aiding them in comprehending the lessons.